UiTM Tapah and Kota Kinabalu Campuses at International Educational Design, Games, Invention, and Innovation 2024 - Elangovan, Tavasuria (Universiti Teknologi MARA, Perak, 2024)
28 October 2024 – The FSG team from UiTM Perak Branch, Tapah Campus, and UiTM Sabah Branch, Kota Kinabalu Campus won the Silver Award at the International Educational Design, Games, Invention, and Innovation 2024 (iEDGII2024). The Universiti Teknologi MARA Johor Branch, Pasir Gudang Campus, hosts this international competition from 1st July 2024 to 22ndSeptember 2024, followed by a judging period from 10 October 2024 to 23 October 2024. On October 28, 2024, the results and awards were announced through YouTube Live. The main theme of the competition is Innovative Excellence in Education: Pioneering Inclusive Learning.